Stitching rites : colcha embroidery along the northern Rio Grande - MacAulay, Suzanne P. (Suzanne Pollock), 1943- (University of Arizona Press, 2000)
"Colcha embroidery is a traditional Spanish colonial style of textile, bed covering, or wall hanging dating from the early nineteenth century. In the first book to consider this craft, Suzanne P. MacAulay provides a detailed account of this folk art tradition that is both old and constantly renewing itself, presenting a sensitive portrayal of artists and the contexts in which they live and work." "Stitching Rites reveals how art, history, and memory interweave in a rich creative web. Based on archival research and extensive interviews with the artists, the book reveals the personal motivations of the embroiderers and their relationships with their work, with each other, with their community, and with outsiders."--Jacket